2015
DOI: 10.1371/journal.pone.0129768
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir Prophylaxis Reduces Inflammation and Facilitates Establishment of Cross-Strain Protective T Cell Memory to Influenza Viruses

Abstract: CD8+ T cells directed against conserved viral regions elicit broad immunity against distinct influenza viruses, promote rapid virus elimination and enhanced host recovery. The influenza neuraminidase inhibitor, oseltamivir, is prescribed for therapy and prophylaxis, although it remains unclear how the drug impacts disease severity and establishment of effector and memory CD8+ T cell immunity. We dissected the effects of oseltamivir on viral replication, inflammation, acute CD8+ T cell responses and the establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Indeed these data agree with recent findings that functional memory CD8 + T cells established during oseltamivir prophylaxis for IAV infection, which reduced inflammation during the acute phase of infection, were still capable of mounting robust recall responses. 38 Our study is also the first to show the converse in that, expression of the viral virulence protein PB1-F2 by a heterosubtypic challenge virus that displays heightened pathophysiology of disease, does not compromise the capacity to recall pre-existing memory CD8 + T cells essential for clearance of this serologically distinct virus. These findings highlight the importance of maintaining cross-reactive memory CD8 + T-cell pools, as these are expected to be effective at promoting viral clearance on encounter with highly inflammatory pandemic strains.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed these data agree with recent findings that functional memory CD8 + T cells established during oseltamivir prophylaxis for IAV infection, which reduced inflammation during the acute phase of infection, were still capable of mounting robust recall responses. 38 Our study is also the first to show the converse in that, expression of the viral virulence protein PB1-F2 by a heterosubtypic challenge virus that displays heightened pathophysiology of disease, does not compromise the capacity to recall pre-existing memory CD8 + T cells essential for clearance of this serologically distinct virus. These findings highlight the importance of maintaining cross-reactive memory CD8 + T-cell pools, as these are expected to be effective at promoting viral clearance on encounter with highly inflammatory pandemic strains.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, oseltamivir alone appeared sufficient to reduce pulmonary IL‐6 and TNFα levels and no additional effect was observed when it was combined to azithromycin. Prior studies have already shown that oseltamivir could act as an anti‐inflammatory agent reducing cytokine production and activation/migration of pro‐inflammatory immune cells such as neutrophils or macrophages in lungs with a marginal control of pulmonary viral replication . These results could explain the good protection conferred by oseltamivir monotherapy and combined therapy in infected mice despite a weak impact on the lung viral replication (only 3‐ and 3.47‐fold decreases compared to saline, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…Prior studies have already shown that oseltamivir could act as an anti-inflammatory agent reducing cytokine production and activation/migration of pro-inflammatory immune cells such as neutrophils or macrophages in lungs with a marginal control of pulmonary viral replication. 27,28 These results could explain the good protection conferred by oseltamivir monotherapy and combined therapy in infected mice despite a weak impact on the lung viral replication (only 3-and 3.47-fold decreases compared to saline, respectively). Besides the impact of the azithromycin/oseltamivir combination in vivo, it would be interesting to investigate the impact of combining these two compounds in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…A non‐exhaustive list of strategies to induce heterosubtypic immunity against influenza evaluated in ferrets include: HA stem vaccination; prime‐boost with chimeric HA‐based vaccines; use of conserved influenza proteins such as nucleoprotein (NP), matrix‐1 (M1), matrix‐2 (M2) and RNA polymerase subunit B1 (PB1); replication‐deficient viruses; live attenuated formulations; the use of potent adjuvants such as Protollin, glucopyranosyl lipid adjuvant—aqueous formulation (GLA‐AF), CoVaccine HT, cationic adjuvant formulation and poly‐g‐glutamic/chitosan nanogel; Escherichia coli ‐derived vaccines; DNA, mRNA and viral vector vaccines; and the use of virus‐like particles (VLP) . Additional examples of important ferret studies include (but are not limited to) evaluating the influence of changing the route of influenza inoculation on subsequent immunity and the use of neuraminidase (NA) inhibitors as prophylaxis …”
Section: Ferrets For Influenza Surveillance and Vaccine Developmentmentioning
confidence: 99%